Impact of Paratuberculosis on Cattle Production: Comprehensive Strategies for its Control and Prevention. (Veterinary Science, 2025)
The study addresses bovine paratuberculosis, a chronic infectious disease caused by Mycobacterium avium subspecies paratuberculosis, which primarily affects ruminants and has a significant economic impact on milk and meat production. The objective of the research is to analyse current strategies for diagnosis, control, and prevention by identifying their limitations and areas for improvement. To achieve this, a historical literature review was conducted on publications from 2019 to 2024 concerning the disease in cattle. The results reveal that diagnosis is complex due to the subclinical nature of the disease and the pathogen’s resistance. The most commonly used tests are ELISA, PCR, and faecal culture, with PCR standing out for its higher sensitivity. However, no definitive diagnostic test is currently available. Regarding control, the importance of implementing biosecurity measures, monitoring high-risk animals, and isolating infected cows is emphasised. In conclusion, controlling paratuberculosis requires a comprehensive approach that combines early diagnosis, effective biosecurity, and appropriate management. Despite advancements, eradication remains a challenge due to bacterial resistance and the limitations of available tools, highlighting the need for continued research into more effective diagnostic methods and vaccines.
Keywords: Paratuberculosis; Cattle; Control; Disease; Health